Restrictive Deterrence in Drug Offenses: A Systematic Review and Meta-Synthesis of Mixed Studies - Guan, Xin; Lo, T. Wing (Frontiers in Psychology, 2021)
Deterrence by punishment aims to prevent a crime; however, it is not always successful. Restrictive deterrence explains the continuous criminal activities that occur despite deterrence; offenders enact various strategies to avoid detection, which is more typical among drug offenders given that they have a high frequency of offending and exposure to punishment. This systematic review provides an in-depth understanding of restrictive deterrence of drug offenders. Two prominent themes, “restrictive deterrence strategy” and “deterrability and restrictive deterrence,” depict drug offenders’ restrictive deterrence and effectively fit within the certainty–severity framework of punishment. Future studies should investigate restrictive deterrence strategies in the after-arrest context, the facilitative effect of perception of risk on strategy development, and facilitators or inhibitors affecting the diffusion of restrictive deterrence strategies.